JOYFUL LEARNING BERBASIS HYPERCONTENT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH - Moch. Fachri; Abd. Hamid Wahid; Hasan Baharun; Khatijatul Lailiyah (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
This study aims to analyze and understand about hypercontent-based joyful learning in improving student learning motivation in Islamic Religious Education (PAI) learning at Nurul Jadid Paiton Paiton Probolinggo Vocational High School (SMK). Hypercontent-based Islamic Learning (PAI) has an important role in increasing student interest in learning and learning motivation through the joyful learning method. This research uses a qualitative with case study. The data collection technique is done through; interview, observation and documentation. The data analysis was carried out in a circular manner through the stages of presenting research data, reducing data, and drawing conclusions. The results showed that; hypercontent-based joyful learning in increasing learning motivation, including; first, optimization of methods, second, optimizing student understanding through technology, third, achieving goal's education in the form of student art and technology. The implication of this research shows that hypercontent-based joyful learning is categorized as very good and suitable for use in Islamic Religious Education (PAI) learning and can increase student motivation at SMK Nurul Jadid Paiton Probolinggo.